Do footwear styles cause falls or increase falls risk in healthy older adults? A systematic review. (2nd January 2019) - Davis, Annette; Haines, Terry; Williams, Cylie
Abstract : Background and purpose: Falls in older adults is a major issue for health care organisations. Footwear is often reported as a contributing factor to falls in older adults; however, the reporting of footwear styles that are proposed to increase falls and falls risk is confusing. Moreover, these reports have been used to inform falls guidelines and recommendations by health practitioners. A systematic review was performed to identify and synthesize the available evidence examining whether there was support of a causal or correlational relationship between different styles of footwear and falls in older adults in real-life settings. Method: The databases included in the search were Ovid MEDLINE, PubMed, Scopus and Web of Science. The inclusion criteria were papers with falls outcomes, healthy adults that were 65 years or older. The footwear styles included slippers, Oxford/lace ups, high heels, boots and sandals. The exclusion criteria were laboratory studies and papers with primary focus on gait issues that increased falls likelihood. Results and discussion: Nine studies met the inclusion criteria and were included in the review from a total of 363 papers identified in the database search. The results of this review suggest that there is inadequate evidence to link any particular footwear style with falls. However, it may be possible that it was not the style of footwear, rather how accustomed the individual was to wear that particular style of footwear. Conclusion: There is limited evidence supporting footwear recommendations as a discrete falls prevention strategy. Clinicians should be pragmatic in their advice to healthy older adults about footwear styles and their potential to reduce falls or falls risk.